Primates - Burke, Mark; Ptito, Maurice (IntechOpen, 2018)
Nonhuman primates (referred to here as primates) provide an invaluable source of information for a multitude of scientific fields including ecology, evolution, biology, psychology, and biomedicine. This volume addresses various topics related to primate research that includes phylogeny, natural observations, primate ecosystem, sociocognitive abilities, disease pathophysiology, and neuroscience. Topics discussed here provide a platform for which to address human evolution, habitat preservation, human psyche, and pathophysiology of disease.